If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5) + 4 = 5x + -3(2 + x) Reorder the terms: 2(-5 + x) + 4 = 5x + -3(2 + x) (-5 * 2 + x * 2) + 4 = 5x + -3(2 + x) (-10 + 2x) + 4 = 5x + -3(2 + x) Reorder the terms: -10 + 4 + 2x = 5x + -3(2 + x) Combine like terms: -10 + 4 = -6 -6 + 2x = 5x + -3(2 + x) -6 + 2x = 5x + (2 * -3 + x * -3) -6 + 2x = 5x + (-6 + -3x) Reorder the terms: -6 + 2x = -6 + 5x + -3x Combine like terms: 5x + -3x = 2x -6 + 2x = -6 + 2x Add '6' to each side of the equation. -6 + 6 + 2x = -6 + 6 + 2x Combine like terms: -6 + 6 = 0 0 + 2x = -6 + 6 + 2x 2x = -6 + 6 + 2x Combine like terms: -6 + 6 = 0 2x = 0 + 2x 2x = 2x Add '-2x' to each side of the equation. 2x + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 2x + -2x Combine like terms: 2x + -2x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| x+17-4=3+y | | x/6=4=15 | | 8(x-5)+9=8x+2 | | c=17v | | 11x+4y=17 | | 2x+3=2(x+1)1 | | -2x+3x=10 | | -1+15x=15x-1 | | 4x^4y^4+-2xy^2=0 | | 3n-10=21 | | 0=-16t^2+12.51t | | 6000=(40+x)+(40+x)+x+x | | 18b^2+25b-3= | | 10=2(u-5)-6u | | 1474x+4=20 | | 6000=(40+x)(x) | | 0.2(x+60)-0.08(x-30)=8.4 | | 12x+6=8x+42 | | 1/6x-2/7=4/7 | | f(x)=x^2+7x-7 | | (2x+1)(9x+b)=6x^2-5x+c | | 7.93-15.29v=0.66v | | 77=.5(7)(9+b) | | 6000=40w+w^2 | | 2(2c-3)-7=2c+5 | | a/4=32 | | 9x+1.5=19.5 | | -5w+4w^2+9=0 | | 6a-4ifa=7 | | 30-15x+6x=32+16 | | 4x+31=-x+1 | | 4-11=3 |